Assessing the Emotional Response in Social Communication: The Role of Neuromarketing - Zito, Margherita; Fici, Alessandro; Bilucaglia, Marco; Ambrogetti, Francesco S.; Russo, Vincenzo (Frontiers in Psychology, 2021)
Social advertising is designed to have an impact on the target audience behaviour to improve the welfare of both the individuals and the society. The challenge for social marketing, is to respond to the exchange process in a social perspective, considering that non-profit actions are perceived as intangible since they deal with services. As donations, neuroscience applied to consumer behaviour is an added value since it offers elements explaining the individuals’ reactions to emotional contents. Understanding the emotions in the moment in which they are felt, allows to understand the experimentation of a message by individuals and to understand the possibility that the message can change the behaviour of the target audience. The aim of the study was to assess the effectiveness of the Unicef bequests campaign in terms of emotional response, comparing different creative proposals to optimize communication, applying neuromarketing tools to the social area. The experiment involved 70 subjects (35 males; 35 females; mean age 68.94 years) and compared two different spots and flyers. Progeny factor was introduced to assess the different impact of bequests depending on the presence or absence of potential heirs. Instrumentation involved neuromarketing tools such as EEG, SC and eye-tracker. Analysis of the two spots showed statistically significant differences in both the AWI, for the cognitive involvement, and the SC, the emotional activation indicator, particularly for those not having children (target audience) and in a specific spot linked the possibility to continue living after death. The detection of the emotional responses through neuromarketing tools, associated to non-profit communication, resulted particularly effective and verified an increment of 35% of the donations. Analyses performed with neuromarketing techniques allowed to understand both emotional intensity and cognitive involvement and to understand the best solution, according to the target audience and to the aim of Unicef.